Side profile facial recognition using CNN - Varthamanan Manisha (Nanyang Technological University, 2024)
Facial recognition is rapidly advancing in the field of Artificial Intelligence (AI) and according to Statista, the market size is projected to reach US$5.71B in 2024 for facial recognition [1]. It is used across various domains such as security, law enforcement, and healthcare. The current systems work well with the front view of a person as only the frontal image is used in the training data of these systems. However, it is challenging in real-world scenarios as it is common for people to be seen from various angles. Thus, a robust facial recognition system that could identify a person from side and front would reduce challenges faced in various applications. This project researched and trained a side profile facial recognition system using CNN to learn the unique facial features.